2021
DOI: 10.3324/haematol.2020.263715
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with ibrutinib does not induce a <I>TP53</I> clonal evolution in chronic lymphocytic leukemia

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Brieghel and colleagues 20 did find that excluding TP53 ‐m with a VAF < 1% did not affect predictive performance for patients treated with ibrutinib. We captured VAF dynamics of TP53 ‐m in a minority of patients only, though other studies suggest that clonal expansion of TP53 ‐m during treatment with targeted therapy (unlike CIT) is uncommon and not associated with inferior outcomes 18,31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brieghel and colleagues 20 did find that excluding TP53 ‐m with a VAF < 1% did not affect predictive performance for patients treated with ibrutinib. We captured VAF dynamics of TP53 ‐m in a minority of patients only, though other studies suggest that clonal expansion of TP53 ‐m during treatment with targeted therapy (unlike CIT) is uncommon and not associated with inferior outcomes 18,31 …”
Section: Discussionmentioning
confidence: 99%
“…We captured VAF dynamics of TP53-m in a minority of patients only, though other studies suggest that clonal expansion of TP53-m during treatment with targeted therapy (unlike CIT) is uncommon and not associated with inferior outcomes. 18,31 Studies demonstrating the efficacy of the combination BTKi + VEN in treatment naïve CLL continue to be reported, but whether a fixed duration of combination therapy (that may be associated with increased toxicity) has advantages over sequencing novel agents or over continuous BTKi is still unknown. This is particularly pertinent to patients with high-risk genomics.…”
Section: (B) (A)mentioning
confidence: 99%
“…A small proportion of TP53 mutations increased. After a prolonged follow-up of greater than 2 years, the overall stability of low-burden TP53 mutations was noted, supporting the notion of the lack of specific positive selection of TP53 mutations under conditions of ibrutinib treatment (31). Nevertheless, all these observations need to be confirmed in a cohort of patients treated with novel agents in the frontline setting.…”
Section: Impact Of Targeted Agents On Low-burden Tp53 Mutationsmentioning
confidence: 68%
“…Given that TP53-mutated patients can benefit from targeted therapies with improved remission duration, there is a need to evaluate the impact of these therapies on the evolution of the TP53-mutated clone. Data on the clonal evolution of low-burden TP53 mutations upon targeted treatment are limited (23,31). Malcikova et al showed that upon the use of BcR or bcl2 inhibitors as a second line of treatment, the percentage of VAF in the residual lymphocytosis remains stable, which reflects the efficacy of these treatments on the mutated clones (23).…”
Section: Impact Of Targeted Agents On Low-burden Tp53 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation